A belief in socioeconomic mobility promotes the development of academically motivating identities among low-socioeconomic status youth. Issue 1 (2nd January 2022) - Browman, Alexander S.; Svoboda, Ryan C.; Destin, Mesmin
ABSTRACT: Despite barriers to educational attainment, low-SES youth often maintain strong academic intentions and performance if they continue to view school as important for obtaining the desired futures they envision for themselves. We undertook three related studies to examine the importance of one aspiration central to the desired futures of many low-SES youth: attaining upward socioeconomic mobility. Cross-sectional, longitudinal (Study 1), and experimental data (Study 2) demonstrate that low-SES youth's beliefs about their likelihood of attaining mobility affects their likelihood of envisioning futures that hinge on educational attainment, which ultimately predict their academic intentions and performance. Study 3 then tests a novel intervention for promoting the adoption of education-dependent futures among low-SES youth: highlighting multiple viable school-based paths to future mobility.